"Is This a Chapter Book?": Parent-Involved Categorization in a Kindergarten Classroom Book Collection. Issue 2 (3rd April 2019) - Holstrom, Chris
Abstract: Many primary school classrooms have book collections. Most teachers organize and maintain these collections by themselves, although some involve students in the processes. This qualitative study considers a third approach, parent-involved categorization, to understand how people without library or education training categorize books. We observed and interviewed parents and a teacher who worked together to categorize books in a kindergarten classroom. They employed multiple orthogonal organizing principles, felt that working collaboratively made the task less overwhelming, solved difficult problems pragmatically, organized books primarily to facilitate retrieval by the teacher, and left lumping and splitting decisions to the teacher.